Proposta de índice de correção de chuva (ICC) aplicável aos projetos de captação e aproveitamento de água pluvial - CORREA, Jairo dos Passos (Universidade Federal do Pará, 2018)
The study measure dada of rainfall to determine a rain correction index (rci) applicable in collection projects and rainwater utilization assisted by statistics tests non-parametric, based on assumption that a water line part of rainfall are discarded. The analyses of pluviographic historical set of water lines show that Belem presents large potential to promote rainwater utilization, two periods were identified during the year: a rainier period and a less rainy period. The results present an average of one rainy event per day, from January 2001 to December 2011, around 38% are utilized only to wash the rain water collection system. The Anderson-Darling test revealed the non-adherence of the rain sets in a normal distribution and according to the Mann-Kendall test there wasn’t significant tendency in the evaluated sets. Therefore, after to calculate the effectively rainwater utilization, determination of the rain correction index (rci), the test application of normality and the Kruskal-Wallis variance test, three corrections index that determine the water line effectively usable were proposed: the first during the year (0.78), the second during the most rainy period (0.79) and the third during the less rainy period (0.76).